Edible double-network gels based on soy protein and sugar beet pectin with hierarchical microstructure. (August 2015) - Hou, Jun-Jie; Guo, Jian; Wang, Jin-Mei; He, Xiu-Ting; Yuan, Yang; Yin, Shou-Wei; Yang, Xiao-Quan
Abstract: The sugar beet pectin/soy glycinin (SBP/SG) double network (DN) gel was synthesized by a two-step enzymatic-induced sequential cross-linking strategy. Laccase and microbial transglutaminase (mTGase) were successively employed to the SBP/SG dispersion, so as to induce the formation of the covalent cross-links among the SBP and SG molecules. Uniaxial compression measurements indicated that the DN gels exhibited greater mechanical toughness than the gels with corresponding single network which was only cross-linked by mTGase. Confocal laser scanning microscope (CLSM) and scanning electron microscopy (SEM) observation demonstrated that the phase separation behavior of the two biopolymers at different length scales resulted in the formation of a highly heterogeneous and hierarchical microstructure in the DN gel. The higher structural complexity and mechanical integrity derived from this architecture might be mainly responsible for the enhancement of the gel toughness. A significant decrease of the gel toughness and the disappearance of the hierarchical microstructure were observed in the DN gel prepared by SG and the modified SBP which was subjected to an acidic protease treatment to remove the protein components in SBP. This suggested that the amphiphilic property and the structural heterogeneity of SBP might be the dominant factor in the formation of the unique microstructure in the enzymatic cross-linked protein/polysaccharide DN gel system. These results suggested that the DN principle could widen the texture range of gel-like foods and offer food industry an attractive strategy for developing hierarchical gel architectures via manipulating complex phase separation behavior of protein and polysaccharide. Graphical abstract: Highlights: SBP/SG DN gel was synthesized by a two-step enzyme-induced cross-linking strategy. The first and second network were cross-linked by laccase and mTGase, respectively. The fracture force of DN gels was greater than the SN gels. The enhanced toughness was due to the hierarchical microstructure in the gel.